2010
DOI: 10.1088/2041-8205/722/2/l209
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Influence of Unidentified Binaries on Velocity Dispersion Measurements in Ultra-Faint Stellar Systems

Abstract: Velocity dispersion measurements of recently discovered Milky Way satellites with M V −7 imply that they posses high mass-to-light ratios. The expected velocity dispersions due to their baryonic mass are ∼0.2 km s −1 , but values 3 km s −1 are measured. We perform Monte Carlo simulations of mock radial velocity measurements of these systems assuming that they have mass-to-light ratios similar to globular clusters and posses an unidentified binary star population, to determine if these stars could boost the vel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 43 publications
3
98
0
Order By: Relevance
“…After this, we chose a binary fraction value 8 for Carina of 0.4, because this value produced the Hess diagram models that most resembled the data. This binary fraction is consistent with values obtained in other dwarf galaxies (e.g., McConnachie & Côté 2010;Geha et al 2013). Figure 7 shows the Hess diagram of the data (left panels) and the best-fit model (right panels), as well as the residuals for each Carina region.…”
Section: Resultssupporting
confidence: 88%
“…After this, we chose a binary fraction value 8 for Carina of 0.4, because this value produced the Hess diagram models that most resembled the data. This binary fraction is consistent with values obtained in other dwarf galaxies (e.g., McConnachie & Côté 2010;Geha et al 2013). Figure 7 shows the Hess diagram of the data (left panels) and the best-fit model (right panels), as well as the residuals for each Carina region.…”
Section: Resultssupporting
confidence: 88%
“…For classical dSphs, the above works in the literature investigated the effect of binary systems on velocity second moments and concluded that the influence of binary systems in these dSphs is, in fact, negligible because their intrinsic velocity second moments are much larger than the velocity distributions inflated by binaries. Although not all of the UFD galaxies were investigated for this effect, some authors considered that a binary star is unlikely to make the measured velocity second moments dramatically inflated (see Simon & Geha 2007;Simon et al 2011Simon et al , 2015Koposov et al 2011;Kirby et al 2013;McConnachie & Côté 2010). Therefore, we suppose that the velocity data of each dSph is not affected by the presence of binary stars.…”
Section: Dwarf Spheroidal Galaxy Datamentioning
confidence: 90%
“…Here we stress that velocity dispersions (σ ) are derived from high-resolution individualstar spectroscopy and their errors are indicative. The reliability of these measurements depends on the available number of stars, the possible contaminations from foreground objects and binary stars, and the dynamical state of the galaxy (e.g., Walker et al 2009c;McConnachie & Côté 2010;McGaugh & Wolf 2010;Minor et al 2010).…”
Section: Dwarf Spheroidalsmentioning
confidence: 99%